2018
DOI: 10.1088/1741-2552/aadc1f
|View full text |Cite
|
Sign up to set email alerts
|

Quiet sleep detection in preterm infants using deep convolutional neural networks

Abstract: Our findings suggest that CNN is a suitable and fast approach to classify neonatal sleep stages in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 44 publications
0
59
0
1
Order By: Relevance
“…follow-up, 1 provided the most reliable estimate of a normal developing EEG and has been used extensively in previous studies on preterm brain maturation and sleep staging 23,33,[35][36][37][38] . Consequently, PMA was considered a reasonable estimate of EEG brain-age in this dataset 30 and made it ideal as the training set for the brain-age prediction model.…”
Section: Brain-age Prediction and Deriving Trajectories With A 24-momentioning
confidence: 99%
“…follow-up, 1 provided the most reliable estimate of a normal developing EEG and has been used extensively in previous studies on preterm brain maturation and sleep staging 23,33,[35][36][37][38] . Consequently, PMA was considered a reasonable estimate of EEG brain-age in this dataset 30 and made it ideal as the training set for the brain-age prediction model.…”
Section: Brain-age Prediction and Deriving Trajectories With A 24-momentioning
confidence: 99%
“…Recent research has also shown promising results for CNN-based EEG classification. In seizure detection (Acharya et al, 2018a;Ansari et al, 2018a), depression detection (Liu et al, 2017) and sleep stage classification (Acharya et al, 2018b;Ansari et al, 2018b), CNN have shown promising classification capabilities for EEG data. A CNN for EEG-based speech stimulus reconstruction was presented recently (de Taillez et al, 2017), showing that deep learning is a feasible alternative to linear decoding methods.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the described algorithm is lower compared to state-of-the-art algorithms [13,14,34]. However, there are multiple advantages of the proposed method.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of these approaches are supervised and combine a set of electroencephalography (EEG) features (e.g., temporal features, spectral features, spatial features, complexity features) with a classification algorithm [11,12]. Recently, deep learning has also found its way to sleep staging in preterm infants [13]. Finally, Dereymaeker et al [14] have proposed a cluster-based algorithm for quiet sleep detection.This paper proposes a novel unsupervised method to discriminate quiet sleep from non-quiet sleep in preterm infants.…”
mentioning
confidence: 99%